Amenaza de parto pretérmino asociado a anemia en pacientes de 14 a 28 años ingresadas al Hospital Sagrado Corazón de Jesús periodo enero-junio 2019. - Manrique Ruiz, Evelyn Mileidy (2020)
The threat of preterm birth (PPP) is a worldwide problem due to the high levels of prematurity, about 15 million children are born every year before reaching the end, among the factors that can trigger an APP is anemia due to They started women started pregnancy with low iron stores. The general objective of this research was to determine the association between preterm birth threats and anemia in patients 14 to 28 years of age who were admitted to the Sacred Heart of Jesus hospital in the period January-June 2019. The research method that was specific for the development of this research was the inductive one with the quantitative modality, of transverse-retrospective type, the perspective was based on the observation and compilation of information obtained in the database of the Statistics Department of the HSCJ, formed by a population of 318 patients with threat of preterm birth and by inclusion and exclusion criteria obtain a total of 66 pregnant women who refer to anemia as a second diagnosis which were part of our sample and through which it could be concluded that the incidence of Preterm birth is 58%, which is a relatively high percentage and had a higher prevalence between weeks 32 to 36 .6 of gestation.